Chapter 4 Local Past and Global Present in Plutarch’s Greek, Roman, and Barbarian Questions - Schmidt, Thomas (Teiresias Supplements Online, 2022)
Local Past and Global Present in Plutarch’s Greek, Roman, and Barbarian Questions